German Hitchcock - Klepikov, Milan D. (Iluminace, 2002)
A. Hitchcock's work in Germany in the 1920s, where he worked as a chief decorator and later as a director. Works he participated in Germany and their analysis.
Keywords: British and American director; screenwriter and producer; film producers; film history